Indicator of Rule of Law: Stability of Legislation - Amiryan, Karen (Bulletin of Yerevan University C: Jurisprudence, 2022)
The purpose of this article is to highlight issues related to the stability of legislation. Frequent changes in legislation do not allow ensuring the stability of the legal order. Moreover, not only ordinary laws, but also the Constitution are frequently changed, which cannot contribute to the effective implementation of the principle of the Rule of Law. In the article, the existing problems were highlighted, statistical information was also presented, which helps to better visualize the current situation.We have put forward the concept of sustainable development of legislation, the meaning of which is to ensure a reasonable balance between stability and changes in legislation.
Keywords: Stability of legislation; legislation; stability of law; indicator of Rule of Law; sustainable development of legislation; quality of Law; Constitutional Law; Rule of Law; principles of Law